2008
DOI: 10.1007/s11695-008-9541-8
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid Tumors and Morbid Obesity

Abstract: Carcinoid is a rare gastrointestinal tumor, with an incidence varying from 1 to 2.5 per 100,000 in the general population. In this article, we report an elevated incidence of carcinoid tumor in an obese population, showing the importance of performing an endoscopic procedure before bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Similarly, in our series two of gastric carcinoids were diagnosed out of 863 (0.23%) cases of obese patients who underwent bariatric surgery. This makes the overall incidence 230 per 100,000 population more than the general population and similar to the finding previously reported by Mottin et al [7]. This observation further supports the hypothesis that carcinoid tumor has an association with obesity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, in our series two of gastric carcinoids were diagnosed out of 863 (0.23%) cases of obese patients who underwent bariatric surgery. This makes the overall incidence 230 per 100,000 population more than the general population and similar to the finding previously reported by Mottin et al [7]. This observation further supports the hypothesis that carcinoid tumor has an association with obesity.…”
Section: Discussionsupporting
confidence: 91%
“…In a series of 426 patients who underwent bariatric operation, carcinoid tumor was diagnosed preoperatively in only one patient [4]. Similarly, there were additional four cases reported in the literature [57]. In this paper another two cases of such tumor are reported in two sisters going for sleeve gastrectomy with a review of the previous cases.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although rare in the general population, with an incidence lower than 1 per 100,000 persons, intestinal carcinoid tumors proved to be more frequently diagnosed in obese subjects [20,23,[27][28][29]. In 2002, Keshishan et al [27] reported an incidence of such tumors as high as 1.5% in obese patients.…”
Section: Discussionmentioning
confidence: 99%